Motivações para a (falta de) escolha pela Licenciatura em Educação Física - Gonçalves Júnior, Luiz; Lemos, Fábio Ricardo Mizuno; Corrêa, Denise Aparecida [UNESP] (My University, 2013)
The frequent distortion of the teacher education in Physical Education, associating it with technical and sporting aspects, motivated us to initiate a study aimed at understanding the reasons for this misperception. For this, we performed a theoretical study, based on professional formation in Physical Education in Brazil, together with empirical research, located in the lived experience in a training course for teachers of Physical Education. Thus, the views of the students about the reasons for the choice of course, collected in on a questionnaire and literature review, we show the context of lack of choice, rather than a professional identification.

A frequente descaracterização da Licenciatura em Educação Física, associando-a aspectos técnico-esportivos e de treinamento nos motivou a iniciar um estudo que teve como objetivo a compreensão dos motivos para essa percepção equivocada. Para tal, realizamos um estudo teórico, a partir da temática da formação profissional em Educação Física no Brasil, juntamente com uma pesquisa empírica, situada na experiência vivenciada em um curso de formação de professores de Educação Física. Assim, a partir de relatos discentes, coletados com o uso de questionário, sobre as motivações para a escolha do curso e da revisão de literatura, pudemos sinalizar um panorama da problemática indicada, que apontou para a falta de opção, em detrimento de uma identificação profissional.
Motivations for the choice (or lack of choice) by the teacher formation in physical education
Keywords: Teacher formation; Physical Education; Professional choice; Licenciatura; Educação Física; Escolha profissional